The Role of CD10 Expression in Basal Cell Carcinoma and its mimics: A Clinicopathological Study - Dalya Abdul-Aziz Al-Hamdani; Nadwa Subhi Alazzo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Basal cell carcinoma (BCC) represents the most prevalent form of nonmelanoma skin cancer, predominantly affecting sun-exposed areas with increasing incidence among middle-aged and elderly populations. Specific Background: Accurate histopathological differentiation between BCC and its morphological mimics, particularly trichoepithelioma, remains clinically challenging due to overlapping features, potentially leading to inappropriate therapeutic decisions. CD10, a cell surface marker expressed in various neoplasms and normal skin structures, has emerged as a potential diagnostic tool for distinguishing BCC from histologically similar lesions. Knowledge Gap: The diagnostic utility and expression patterns of CD10 in differentiating BCC from its mimics within Middle Eastern populations remain inadequately characterized. Aims: This study investigated CD10 expression patterns in 50 BCC cases and one trichoepithelioma case, correlating findings with clinicopathological parameters including age, gender, anatomical distribution, and histological variants. Results: Analysis revealed 80% CD10 positivity in tumor cells (32% strongly positive, 48% positive), while 42% showed stromal positivity; nodular BCC comprised 70% of cases, with 84% located in head and neck regions, affecting predominantly middle-aged females. Novelty: This investigation provides novel evidence that CD10 positivity in tumor cells distinguishes BCC from trichoepithelioma, which demonstrates exclusive stromal positivity. Implications: These findings establish CD10 immunohistochemistry as a valuable adjunct marker for resolving diagnostically challenging basaloid proliferations in routine pathological practice.Keywords : CD10 Immunohistochemistry, Basal Cell Carcinoma Diagnosis, Trichoepithelioma Differentiation, Nonmelanoma Skin Cancer, Histopathological MarkersHighlight : Middle-aged adults showed highest lesion frequency, predominantly affecting sun-exposed head and neck regions. Nodular histological pattern represented the most prevalent morphological presentation among examined biopsies. Immunostaining positivity within neoplastic components supported differential diagnosis, while stromal reactivity characterized trichoepithelioma.